2016
DOI: 10.1093/abbs/gmv090
|View full text |Cite
|
Sign up to set email alerts
|

RAS signaling and anti-RAS therapy: lessons learned from genetically engineered mouse models, human cancer cells, and patient-related studies

Abstract: Activating mutations of oncogenic RAS genes are frequently detected in human cancers. The studies in genetically engineered mouse models (GEMMs) reveal that Kras-activating mutations predispose mice to early onset tumors in the lung, pancreas, and gastrointestinal tract. Nevertheless, most of these tumors do not have metastatic phenotypes. Metastasis occurs when tumors acquire additional genetic changes in other cancer driver genes. Studies on clinical specimens also demonstrated that KRAS mutations are presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 178 publications
(215 reference statements)
1
25
0
Order By: Relevance
“…Evidences have shown that Ras mutations frequently occur in glioma. And Ras mutation leads to the activation of a wide range of signaling pathways, including AKT [23], which participate in controlling tumor cells proliferation, death, metastasis, and cell-cycle progression. This here, we found that AKT activation induced by Ras mutation led to the down-regulation of H1.5T10ph, but has no impacts on H1.5 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences have shown that Ras mutations frequently occur in glioma. And Ras mutation leads to the activation of a wide range of signaling pathways, including AKT [23], which participate in controlling tumor cells proliferation, death, metastasis, and cell-cycle progression. This here, we found that AKT activation induced by Ras mutation led to the down-regulation of H1.5T10ph, but has no impacts on H1.5 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in this bacterial taxon's abundance has also been found to be associated with prostate cancer, although the mechanism of action is unknown [59] . We also show that mutations in KMT2C , a gene commonly co-mutated along with KRAS, could be predicted, in part, using the abundance of Ruminococcus [60] . These bacteria have been previously implicated in inflammatory bowel disorders and colorectal cancer by multiple groups [8,[61][62][63] .…”
Section: Discussionmentioning
confidence: 77%
“…Tyrosine kinase inhibitors (TKIs), gefitinib and erlotinib acting as reversible inhibitors for binding to the ATP pocket of the protein tyrosine kinase were clinically approved agents targeting EGFR. In NSCLC, gefitinib was shown to induce partial responses (PR) in approximately 10% of cases [46]. The downstream kinases were also tested as target for therapeutic intervention, resulting in the development of several potent MEK inhibitors [47,48].…”
Section: The Applications Of Components Of Raf-mek-mapk Pathway In Anmentioning
confidence: 99%